The Role of Instagram in Improving English Vocabulary of Generation Z Students at IPB Cirebon - Nisa Hoerunisa; Cici Situmorang; Virdhistie Argarani Ubaedillah; Oktavia Romandi (Journal of Innovative and Creativity, 2026)
This Research explores the efficacy concering the effectiveness of instagram as a resource for English acquisition among Generation Z learners. This Study’s Primary. The main focus is to examine how the platform plays a role in improving vocabulary mastery, particularly in the use of adjectives, and its impact on their linguistic comprehension, particularly the account @dailybahasainggris, in learning English vocabulary, including understanding and using adjectives, among Generation Z students at IPB Cirebon. This Research applied An obseravtional qualitative method, documentation, and semi-structured interviews. Involving 15 Generation Z A student majoring in English Education at IPB Cirebon as research subjects, the findings revealed that Instagram made a positive contribution in facilitating students to understand and remember learning materials, and apply English vocabulary, especially adjectives, through visual content, explanatory text, and examples of word usage in everyday contexts. Features like Reels and image uploads facilitate students in understanding the contextual meaning of adjectives and distinguishing them in English sentences. Moreover, the use of Instagram also increases students' motivation and desire to learn vocabulary because the learning process feels more flexible, relaxed. This, Instagram, particularly the account @dailybahasainggris, can serve as a supportive medium in learning English to enhance students' vocabulary and adjective skills.